INTERDISCIPLINARY APPROACH TO MEASUREMENT OF WELLBEING - Muchova, Eva; Terek, Milan (European Scientific Journal, ESJ, 2013)
The global financial crisis brings a crisis of confidence in the traditional ways of measuring welfare and economic performance. The current methods do not sufficiently take into account the problem of speculative risks, environmental expenses, ethics and subjective well-being. So far, the standard indicators are considered as unsufficient tool of measurement of economic performance and welfare. Economic well-being is a broader concept than GDP, it contributes to categories such as leisure, wealth, non-market activities. On the other hand, welfare is reduced by uncertainty and unemployment. The role of measurement of well-being is not to replace GDP, but the indicators related to well-being, happiness, social development should be an important supplement in order to provides greater insight into the functioning of society. Economics of happiness focused on links between economics and other disciplines, such as psychology and sociology. The paper deals with GDP limits, the concept of happiness and alternative approaches to measurement of individual wellbeing.